ANALISIS NILAI TAMBAH PRODUK OLAHAN SINGKONG PADA IKM DI KABUPATEN TIMOR TENGAH UTARA - Sirilius Nafanu; Felisisima Afoan (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
Agricultural commodities, including cassava, are perishable commodities, so tomaintain their use value, they require processing into certain products. IKM thatprocesses various kinds of chips, one of which is processing cassava into cassavachips. The location of IKM is adjusted to the availability of raw materials, laborand also cassava is one of the processed products into various products, both forstaple foods or snacks. This study aims to analyze the difference in the amount ofadded value obtained from processing cassava into cassava chips in halal-certifiedSMEs in the research area which will be the focus of products in TTU Regency.The method to determine the added value produced from cassava agroindustry intocassava chips is used the value added analysis formula, which will be the focus ofthe product in TTU Regency. The method used for data analysis is quantitativedescriptive analysis. The results showed that the agoindustry of cassava chips atIKM Tiga Saudara and IKM Vita Pung, had a long and continuous term inproducing cassava into cassava chips compared to other agroindustry because ithad a halal certificate.